(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2017)
AEP means auto electro plating. Auto electro plating is used to increase the gorgeous look and also the life of component. Electro plated products are used for wide variety of applications in many industries. Nickel chrome plating is used in automobile industry for increased the product life and gives a bright look. Different plating materials are used on the basis of their properties and conformity for example Gold plating is used for ornaments, copper plating is used for PCB’s, Palladium plating is used in catalytic converters so that they can absorb excess of oxygen that results commonly during the manufacturing of the catalytic converters.